Merdeka Belajar dan Praktik Kerja Lapangan: Mewujudkan Pendidikan Berkualitas Melalui Peningkatan Keaktifan dan Kreativitas Mahasiswa Teologi - Berkatni, Yuli; Rehuellah, Yesyurun Joanne; Panjaitan, Firman (Sekolah Tinggi Teologi Anugrah Indonesia, 2025)
This study analyzes the application of the concept of Free Learning in the practice of fieldwork (PKL) at the College of Theology (STT) to realize quality education in terms of increasing the activeness and creativity of students. Street vendors should ideally be a means for students to integrate theological knowledge with real practice, along with the flexibility and freedom provided by the concept of Free Learning. However, in practice, many times students face obstacles such as limited opportunities to innovate and even labor exploitation, where they are more assigned to jobs that do not correspond to their field of study. This study uses qualitative methods through literature studies, in-depth interviews and observations to identify the relationship between learning freedom and increased student creativity. Although previous studies have shown that innovation in street vendors can increase student engagement, this study shows that challenges in implementation in theological education still exist. The results of this study are expected to provide insights to improve the PKL system in STT, with recommendations to improve cooperation between campus and PKL institutions, as well as create a more supportive environment for student creativity, so that PKL can be a more effective forum for student competence development in accordance with the principle of Free Learning.